Paracoccidioidomycosis: No genetic damage in human peripheral blood cells of patients assessed by single-cell gel (comet) assay - Ribeiro-Vieira, Renata Aparecida Martinez Antunes [UNESP]; Ribeiro, Daniel Araki; Salvadori, Daisy Maria Favero [UNESP]; Marques, Silvio Alencar [UNESP] (FapUNIFESP (SciELO), 2007)
Paracoccidioidomycosis is a systemic fungal infection caused by Paracoccidioides brasiliensis. As infectious diseases can cause DNA damage, the authors aimed at analyzing DNA breakage in peripheral blood cells of patients with paracoccidioidomycosis by using the comet assay. The results suggested that paracoccidioidomycosis does not cause genotoxicity.
Keywords: Comet assay; DNA; Genotoxicity; Paracoccidioides brasiliensis; Paracoccidioidomycosis; adult; analysis of variance; analytic method; blood cell; clinical article; comet assay; comparative study; controlled study; DNA damage; DNA strand breakage; genotoxicity; human; mycology; serology; South American blastomycosis; Adult; Comet Assay; DNA Damage; Humans; Leukocytes, Mononuclear